Information power school library media program guidelines : national teleconference. ([Columbia, S.C.] University of South Carolina, 1986)
A program on the techniques, technology and the impact of information centers of school libraries. It discusses national guidelines being adopted in implementing school library media program.
Keywords: Media programs (Education).; Education; Library science